The Impact of Violence Against Physicians on the Career Choices of Medical Students at Manisa Celal Bayar University Faculty of Medicine - Özdemir, Muhammed Alp; Karabağ, Gökmen (The Bulletin of Legal Medicine, 2024)
Objective: The violence in healthcare is any verbal, behavioural threat or physical attack that endangers the healthcare worker by patients, their relatives or another person. In this study, we aim to assess how the attitudes of the medical students are shaped towards violence against physicians and how the violence in healthcare affects their area of expertise, working environment and future and we want to show the effect of the violence in healthcare on the medical students’ career plans and discuss the measures against the healthcare violence. Methods: A questionnaire was prepared for 983 students studying at Manisa Celal Bayar University Faculty of Medicine between 01.07.2019 08.10.2019 in the 2019-2020 academic year. Data were analyzed using the Statistical Package for Social Sciences 21.0. Results: We determined that 54.9% of the medical students who cooperated in our study were female, with an average age of 20.83±2.05, 59.9% preferred medical school to be a physician. Our results showed that 15.9% of the participants experienced violence against physicians. They experienced violence particularly in the emergency service; verbal violence was the most common. 93% of them found the measures taken were inadequate. Besides, with the increase of term, students started to prefer internal branches over surgical branches. Conclusion: We show that violence against physicians significantly influences the preferences of medical students. The best option for our country will be the correct implementation of the measures and rearrangement and execution of systematic and legal infrastructure against the violence.